(untitled) (Filološke studije, 2019)
Folklore therapy is a relatively new scientific discipline. Its subject of interest and research is the impact of folklore (meaning the practice of folklore dances and songs) on people’s health, and also the way folklore has an impact on individual subjects in their social environments, or the power of folklore as a corrective tool for human behavior in people with psychological disorders. In other words, the relation and connection between folklore and psychology and its application for psychotherapeutic purposes. Hence , we can establish that the folklore here plays a triple role: 1. As a therapeutic tool for medical purposes, treating certain physical anomalies in the client; 2. As a corrective tool for psychotherapeutic purposes, treating mental disorders; and 3. As a preventive tool for medical and non-medical objectives, maintaining and improving the general health condition (both physical as well as mental) of healthy individuals. Traditionally, the Macedonian folklore throughout the centuries has reflected the mental structure of the Macedonian man as a separate ethnos and his subsistence in this area. All the capabilities of the individual for a healthy development in all stages of life is displayed via the practices. Through the mores where rituals such as, for example, weddings, Saints days, the general national festivities, burials and so on are performed, the Macedonian man evinces his conformity with the society and the cultural norms and traditions in these areas.